Answer:
9^2= (x+2)^2+(y+8)^2
Step-by-step explanation:
The equation is r^2=(x+h)^2+(y-k)^2
let's firstly convert the mixed fractions to improper fractions and then proceed.
![\stackrel{mixed}{4\frac{1}{2}}\implies \cfrac{4\cdot 2+1}{2}\implies \stackrel{improper}{\cfrac{9}{2}}~\hfill \stackrel{mixed}{1\frac{1}{4}}\implies \cfrac{1\cdot 4+1}{4}\implies \stackrel{improper}{\cfrac{5}{4}} \\\\[-0.35em] ~\dotfill](https://tex.z-dn.net/?f=%5Cstackrel%7Bmixed%7D%7B4%5Cfrac%7B1%7D%7B2%7D%7D%5Cimplies%20%5Ccfrac%7B4%5Ccdot%202%2B1%7D%7B2%7D%5Cimplies%20%5Cstackrel%7Bimproper%7D%7B%5Ccfrac%7B9%7D%7B2%7D%7D~%5Chfill%20%5Cstackrel%7Bmixed%7D%7B1%5Cfrac%7B1%7D%7B4%7D%7D%5Cimplies%20%5Ccfrac%7B1%5Ccdot%204%2B1%7D%7B4%7D%5Cimplies%20%5Cstackrel%7Bimproper%7D%7B%5Ccfrac%7B5%7D%7B4%7D%7D%20%5C%5C%5C%5C%5B-0.35em%5D%20~%5Cdotfill)
![\begin{array}{ccll} miles&hours\\ \cline{1-2} \frac{9}{2}&\frac{5}{4}\\[1em] x&1 \end{array}\implies \cfrac{~~ \frac{9}{2}~~}{x}=\cfrac{~~ \frac{5}{4}~~}{1}\implies \cfrac{~~ \frac{9}{2}~~}{\frac{x}{1}}=\cfrac{5}{4}\implies \cfrac{9}{2}\cdot \cfrac{1}{x}=\cfrac{5}{4} \\\\\\ \cfrac{9}{2x}=\cfrac{5}{4}\implies 36=10x\implies \cfrac{36}{10}=x\implies \cfrac{18}{5}=x\implies 3\frac{3}{5}=x](https://tex.z-dn.net/?f=%5Cbegin%7Barray%7D%7Bccll%7D%20miles%26hours%5C%5C%20%5Ccline%7B1-2%7D%20%5Cfrac%7B9%7D%7B2%7D%26%5Cfrac%7B5%7D%7B4%7D%5C%5C%5B1em%5D%20x%261%20%5Cend%7Barray%7D%5Cimplies%20%5Ccfrac%7B~~%20%5Cfrac%7B9%7D%7B2%7D~~%7D%7Bx%7D%3D%5Ccfrac%7B~~%20%5Cfrac%7B5%7D%7B4%7D~~%7D%7B1%7D%5Cimplies%20%5Ccfrac%7B~~%20%5Cfrac%7B9%7D%7B2%7D~~%7D%7B%5Cfrac%7Bx%7D%7B1%7D%7D%3D%5Ccfrac%7B5%7D%7B4%7D%5Cimplies%20%5Ccfrac%7B9%7D%7B2%7D%5Ccdot%20%5Ccfrac%7B1%7D%7Bx%7D%3D%5Ccfrac%7B5%7D%7B4%7D%20%5C%5C%5C%5C%5C%5C%20%5Ccfrac%7B9%7D%7B2x%7D%3D%5Ccfrac%7B5%7D%7B4%7D%5Cimplies%2036%3D10x%5Cimplies%20%5Ccfrac%7B36%7D%7B10%7D%3Dx%5Cimplies%20%5Ccfrac%7B18%7D%7B5%7D%3Dx%5Cimplies%203%5Cfrac%7B3%7D%7B5%7D%3Dx)
If you put brackets around (2+1), your method of working is:
1) 15-4*(2+1)=3
2) 15-4*3=3
3) 15-12=3
You don't need any more brackets, as the BIDMAS (brackets, Indices, division, multiplication, addition, subtraction) rule does the rest of the job for you.
The answer is therefore: 15-4*(2+1)=3
Answer:
a. (2,5)
b. (14,15.5)
Step-by-step explanation:
a.
y=4x-3
y=-2x+9
Set both equations equal to each other to solve for x.
4x-3=-2x+9
6x=12
x=2
Plug in x to solve for y.
y=4x-3
y=4(2)-3
y=8-3
y=5
(2,5)
b.
y=(5/4x)-2
y=(-1/4x)+19
Set both equations equal to each other to solve for x.
(5/4x)-2=(-1/4x)+19
4((5/4x)-2=(-1/4x)+19)
5x-8=-x+76
6x=84
x=14
Plug in x to solve for y.
y=(5/4x)-2
y=(5/4(14))-2
y=17.5-2
y=15.5
(14,15.5)